1997
DOI: 10.1007/bf02815125
|View full text |Cite
|
Sign up to set email alerts
|

Lead-induced abnormalities in blood-brain barrier permeability in experimental chronic toxicity

Abstract: The aim of this paper was to determine whether prolonged drinking of lead acetate-containing water by adult rats, which imitates environmental exposure to lead (Pb), affects some morphological and biochemical properties of rat brain microvessels. We noted a significant increase of lead level in capillaries and synaptosomes obtained from brains of rats under chronic toxicity conditions. Intravenously injected horseradish peroxidase (HRP) was used to evaluate the functional state of the blood-brain barrier (BBB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Pb 2+ uptake through the blood-brain barrier proceeds at an appreciable rate, consistent with its action as a potent central neurotoxin (Smith et al, 1997). Although severe lead poisoning may compromise the barrier's integrity, and significant abnormalities following Pb 2+ administration have been reported (Struzynska et al, 1997), there is little evidence that l l Pb 2+ can damage the functions of the blood-brain barrier at a dose <80 μg/dl (Bradbury and Deane, 1993), i.e. at doses that mediate chronic or subacute poisoning.…”
Section: Pathways Of Pb 2+ Entrance Into the Brainmentioning
confidence: 91%
“…Pb 2+ uptake through the blood-brain barrier proceeds at an appreciable rate, consistent with its action as a potent central neurotoxin (Smith et al, 1997). Although severe lead poisoning may compromise the barrier's integrity, and significant abnormalities following Pb 2+ administration have been reported (Struzynska et al, 1997), there is little evidence that l l Pb 2+ can damage the functions of the blood-brain barrier at a dose <80 μg/dl (Bradbury and Deane, 1993), i.e. at doses that mediate chronic or subacute poisoning.…”
Section: Pathways Of Pb 2+ Entrance Into the Brainmentioning
confidence: 91%
“…This, however, is inconsistent with clinical observations that chronic lead exposure increases intracranial pressure (Braun and Gutjahr, 1971;Teo et al, 1997). One possible explanation for the latter findings is that chronic administration of lead may cause blood brain barrier dysfunction (Struzynska et al, 1997), resulting in "leaky" microvessels and increase in membrane permeability.…”
Section: Effect Of Lead On Cerebral Neurogenic Vasodilation 1129mentioning
confidence: 99%
“…The high vulnerability of children's brain to Pb toxicity could be partly attributed to the less welldeveloped brain barrier system, or a possibly high sensitivity of their BBB to Pb insults. Evidence has suggested that Pb can directly act on the barrier structure to increase the permeability of the BBB (Bradbury and Deane, 1993;Dyatlov et al, 1998;Kerper and Hinkle, 1997;Press, 1985;Struzynska et al, 1997;Sundstrom et al, 1985). Others have suggested that the growing capillaries may be the primary target to Pb action.…”
Section: Discussionmentioning
confidence: 99%
“…Children are particularly vulnerable to Pb toxicities for several reasons (Leggett, 1993;Cory-Schlecta and Schaumburg, 2000): they absorb the ingested Pb from the gastrointestinal tract better than do the adults; a greater proportion of systemically circulating Pb gains access to the brain more easily in children, especially those of 5 years old or younger, than in adults; and the developing nervous system in children is far more sensitive to Pb toxicity than the mature adult brains. Evidence in literature also suggests that at low concentrations, Pb disrupts normal blood-brain barrier (BBB) function, resulting in regionally specific increases in permeability to plasma proteins (Dyatlov et al, 1998;Moorhouse et al, 1988;Struzynska et al, 1997;Sundstrom et al, 1985).…”
Section: Introductionmentioning
confidence: 99%